Remediation approaches for polycyclic aromatic hydrocarbons (PAHs) contaminated soils: Technological constraints, emerging trends and future directions - Kuppusamy, Saranya; Thavamani, Palanisami; Venkateswarlu, Kadiyala; Lee, Yong Bok; Naidu, Ravi; Megharaj, Mallavarapu (Chemosphere (Oxford), 2017)
For more than a decade, the primary focus of environmental experts has been to adopt risk-based management approaches to cleanup PAH polluted sites that pose potentially destructive ecological consequences. This focus had led to the development of several physical, chemical, thermal and biological technologies that are widely implementable. Established remedial options available for treating PAH contaminated soils are incineration, thermal conduction, solvent extraction/soil washing, chemical oxidation, bioaugmentation, biostimulation, phytoremediation, composting/biopiles and bioreactors. Integrating physico-chemical and biological technologies is also widely practiced for better cleanup of PAH contaminated soils. Electrokinetic remediation, vermiremediation and biocatalyst assisted remediation are still at the development stage. Though several treatment methods to remediate PAH polluted soils currently exist, a comprehensive overview of all the available remediation technologies to date is necessary so that the right technology for field-level success is chosen. The objective of this review is to provide a critical overview in this respect, focusing only on the treatment options available for field soils and ignoring the spiked ones. The authors also propose the development of novel multifunctional green and sustainable systems like mixed cell culture system, biosurfactant flushing, transgenic approaches and nanoremediation in order to overcome the existing soil- contaminant- and microbial-associated technological limitations in tackling high molecular weight PAHs. The ultimate objective is to ensure the successful remediation of long-term PAH contaminated soils. [Display omitted] •Summary of the extent and status of global PAHs contamination in soil.•Overview of established remediation approaches for PAHs and their costs.•Indication of emerging options for the cleanup of PAHs polluted sites.•Proposal of novel multifunctional green and sustainable cleanup systems for future.•Focus only on the treatment of field soils and not spiked soils.